ISOLATION AND IDENTIFICATION OF BRUCELLA SPECIES FROM SUSPECTED BIOLOGICAL SAMPLES OF HUMAN PATIENTS AND INFECTED ANIMALS BY CONVENTIONAL ISOLATION METHOD FOLLOWED BY PCR ASSAY - N. MADHUKAR; K. BALAKRISHNA; S. PAUL; M. KADAGI; H.S. MURALI; H.V. BATRA (International Journal of Pharma and Bio Sciences, 2014)
Brucellosis is an infectious zoonotic disease of domestic and wild animals. It has a serious implication on human health as well as on the economic development in a developing country like India. Rapid identification and treatment of the disease in human and animal is important for the prevention of spreading the disease. Isolation with a conventional bacteriological method for the identification of the disease stands gold standard, but is time consuming and misleading sometimes. Isolation and identification by conventional PCR assay have been done for screening of Brucella abortus, Brucella melitensis and Brucella suis from suspected samples collected from hospitals and local animal farms. In conclusion, six B. melitensis, four B. abortus, and two B. suis isolate has been identified out of 250 animal biological samples and three B. melitensis and two B. abortus isolates were identified out of seven suspected human blood samples.